2020
DOI: 10.1371/journal.pone.0240026
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of astigmatism outcomes after horizontal rectus muscle surgery in patients with intermittent exotropia

Abstract: This study examined the factors affecting corneal curvature change after lateral rectus recession and medial rectus resection surgery in patients with intermittent exotropia. This was a retrospective cross-sectional study in intermittent exotropia patients who underwent rectus resection surgery. The study involved 41 male and 42 female patients (mean age: 9.55 ± 5.03 years, range: 3-28 years). Corneal astigmatism analysis was performed using the Galilei G4 Dual Scheimpflug Analyzer. The values of simulated and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…At present, there is no unified conclusion about the change trend, duration, and whether there are different changes in refractive state and corneal curvature caused by strabismus correction. Most of the literature on changes in refraction after strabismus surgery shows that changes in the equivalent spherical lens, drift toward myopia, and an increase in astigmatism can be observed after strabismus surgery [5][6][7][8][9]. Some studies showed that changes in myopia and astigmatism were not statistically significant [19], while others found that changes in myopia drift and astigmatism generally returned to the preoperative level within 3-12 months of follow-up, and some studies described continuous changes [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there is no unified conclusion about the change trend, duration, and whether there are different changes in refractive state and corneal curvature caused by strabismus correction. Most of the literature on changes in refraction after strabismus surgery shows that changes in the equivalent spherical lens, drift toward myopia, and an increase in astigmatism can be observed after strabismus surgery [5][6][7][8][9]. Some studies showed that changes in myopia and astigmatism were not statistically significant [19], while others found that changes in myopia drift and astigmatism generally returned to the preoperative level within 3-12 months of follow-up, and some studies described continuous changes [5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Although HOAs affect visual imaging quality, previous studies have mainly dealt only with refractive errors after strabismus surgery, not HOAs. ere are reports that surgery can cause transient myopic drift or lead to astigmatism and axial changes in patients, but the effects are transient and reversible [5][6][7][8][9], while others believe that surgery may cause long-term irreversible refractive changes [10]. Some investigators have also not observed differences in equivalent spherical lenses in strabismus surgery [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A procedure on the horizontal extraocular muscle can correct exodeviation by altering the action of the extraocular muscle. However, it can also cause changes in the refractive error by reducing the tension of the extraocular muscle transmitted through the sclera to the cornea [ 3 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have described changes in spherical equivalent after horizontal muscle surgery. Most of them reported a postoperative myopic shift [ 6 10 ], although some showed a hyperopic shift or no significant change in spherical equivalent [ 11 , 12 ]. As with the spherical equivalent, an increase in with-the-rule (WTR) astigmatism has been reported in the majority of studies [ 6 9 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation